Memorial Plaques in Urban Space of East-European Cities: Case of Kharkiv - Вовк, Ольга Ігорівна; Куделко, Сергій Михайлович (My University, 2022)
The present research deals with study of memorial plaques as one of the most widespread commemoration signs in urban space of East-European cities. Kharkiv was selected as an example because of what it is the second largest city in Ukraine, the industrial, scientific, educational and cultural giant that is currently undergoing severe destruction and damage as a result of hostilities. Main species features of memorial plaques as historical sources as well as local history signs are characterized taking into account the Ukrainian traditions of their establishment and existence. Specific attributes that distinguish these objects from other signs of commemoration are emphasized; the authors’ scheme of their typology is described. Evolution of trends regarding their visual design and approaches to the formulation of devotional texts are observed in a century-old retrospective (from the 1920s to the 2020s). The local pantheon of heroes whose names were immortalized by plaques is analyzed. Points of the topographic distribution of these objects in the city districts are identified. It is shown that plaques can be markers of political and ideological confrontation in crisis times. It is forecasted in what way may evolve a complex of these commemoration signs in the postwar period in Kharkiv.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; memorial plaque; commemoration; East Europe; Kharkiv; urban studies